Tinjauan Yuridis Sosiologis Perlindungan Identitas Anak Korban Kejahatan Seksual : (Studi Putusan Nomor 408/ Pid.Sus/2021/PN Mlg, Studi Putusan Nomor 673 /Pid.Sus/2019/PN Mlg, Dan Studi Putusan Nomor 572/ Pid.Sus/2021/PN Mlg) - Clarysa Dwi Rahmawati; Wasis Suprayitno; Kukuh Dwi Kurniawan (Universitas Muhammadiyah Malang, 2022)
Legal protection for children who are victims of sexual crimes is a manifestation of the obligations given by the State specifically. One of these protections is the protection of the confidentiality of the identity of children who are victims of sexual crimes. This embodiment aims to prevent children from negative treatment from any party that can adversely affect their growth and development of children. It has been explained in the provisions of law No. 11 of 2012 concerning the Juvenile Criminal Justice System Articlen19 paragraph (1). However, there are still many identities of children in conflict with the law that are not kept secret in case decisions are published on the Supreme Court Decision Directory Site. Therefore, the researchers raised two problem formulations. First, how to protect the identity of child victims of sexual crimes according to the laws and regulations. Second, how to protect the identity of child victims of sexual crimes according to the Malang District Court Class IA. The research method used a sociological juridical approach to collect literature study materials and interviews. Conclusions and suggestions from writing this final project, namely Article 19 of Law Numbern11 ofn2012 concerning the Criminal Justice System regarding the identity of children who are victims of sexual crimes whose identities are published if there are parties who violate the law that has set them up. Strict sanctions.